Gastric per-oral endoscopic myotomy (G-POEM) for the treatment of gastric sleeve stenosis: a feasibility and safety study - Zhang, Linda Y.; Canto, Marcia I.; Schweitzer, Michael A.; Khashab, Mouen A.; Kumbhari, Vivek (Endoscopy, 2021)
Background Traditional endoscopic treatments have limited success in gastric sleeve stenosis (GSS). Gastric peroral endoscopic myotomy (G-POEM) could conceivably obliterate the twist/angulation that causes GSS through a tunneled stricturotomy. We report early outcomes of G-POEM for GSS treatment.Methods We retrospectively reviewed all patients with GSS treated with G-POEM at our center. The primary end point was clinical success, defined as symptom improvement with resumption of adequate oral intake, without requiring further intervention.Results 13 patients (mean age 43 ± 10.9 years; 12 female) underwent G-POEM for predominantly helical (11/13, 85 %) GSS. Three (23 %) had concurrent sleeve leak and 10 (77 %) had prior GSS treatment. Two intraoperative complications occurred, with no deviation to the procedure; no major complications occurred. At median follow-up of 175 (interquartile range [IQR] 119–260) days, clinical success was achieved in 10 patients (77 %). Median Gastroparesis Cardinal Symptom Index score in responders decreased from 2.06 (IQR 1.5–2.8) to 0.39 (IQR 0.2–0.5). Three patients (23 %) required surgical revision.Conclusions G-POEM was feasible and safe, and may provide an alternative option for those averse to undergoing surgical revision for treatment of GSS.